Multimodal Interventions Are More Effective in Improving Core Symptoms in Children With ADHD - Ning, Ke; Wang, Tingzhao (Frontiers in Psychiatry, 2021)
Objective: To investigate the effect of sensory integration training combined with EEG biofeedback on core symptoms in children with ADHD. Methods: Fifty-six children with attention-deficit, hyperactive-impulsive and compound ADHD were selected. They were randomly divided into control group, sensory integration training group, EEG biofeedback group, and sensory integration training + EEG biofeedback group, and after 4 months of intervention, concentration time and impulsive- hyperactivity and hyperactivity index scores on the PSQ scale were assessed. Results: Compared with that before the intervention, the attention time was significantly increased (P<0.01), and the impulsive-hyperactivity and hyperactivity index scores were significantly decreased (P<0.05, P<0.01). After the intervention, the attention time was significantly higher than that of the control group (P<0.05, P<0.01), the attention time of the comprehensive intervention group was significantly higher than that of the single intervention group (P<0.01), and the impulsive-hyperactivity and hyperactivity index scores were significantly lower than those of the single intervention group (P<0.05). Conclusion: Comprehensive intervention can significantly improve the concentration level of children with ADHD, and significantly improve the behavioral symptoms of impulsive-hyperactivity and hyperactivity. Comprehensive interventions were more effective than single interventions in improving core symptoms in children with ADHD.